Multi-Year Observations of Fluorescence and Backscatter at the Southern Ocean Time Series (SOTS) Shed Light on Two Distinct Seasonal Bio-Optical Regimes - Schallenberg, Christina; Harley, James W.; Jansen, Peter; Davies, Diana M.; Trull, Thomas W. (Frontiers in Marine Science, 2019)
This work presents insights from 6 years of chlorophyll-a fluorescence and backscatter (700 nm) data at the Southern Ocean Time Series (SOTS) moorings, located in the Subantarctic Zone southwest of Tasmania. Using local calibrations from available voyage data, the fluorescence and backscatter records were related to chlorophyll-a (Chl) and particulate organic carbon (POC), allowing us to estimate and interpret carbon:Chl ratios. Surprisingly, observed carbon:Chl ratios were higher in winter than in summer, indicating that photo-acclimation of phytoplankton to decreased light levels in the deep winter mixed layer is not the main signal. Instead, the data suggest a seasonal succession of two trophodynamic regimes at SOTS: a phytoplankton-dominated community in summer, while in winter the proportion of “non-phytoplankton” POC increases. The two regimes can also be differentiated in an optical index based on fluorescence and backscatter, indicating two distinct bio-optical populations. Seasonal iron limitation and deep winter mixing in the SAZ, reaching as deep as 600m, likely play key roles in setting the stage for the observed ecological succession of the two trophodynamic regimes.